Art Therapy for Paediatric Pain: A Scoping Review - Sofia Olaizola; Chitra Lalloo; Victoria Vickers; Lauren Kelenc; Sakib Tariq; Stephen C. Brown; Jennifer N. Stinson (MDPI AG, 2024)
Pain is common in paediatric populations and is best treated with a multi-disciplinary approach. Art therapy interventions are gaining popularity in paediatrics; however, there is limited evidence on its impact on pain outcomes in children and adolescents. The objective of this scoping review is to map current research on art therapy's impact as an intervention in paediatric populations experiencing any type of pain (i.e., acute, recurrent, and chronic). Electronic searches were conducted by a medical librarian to identify studies that used art therapy interventions in paediatric populations with pain as an outcome measure. Four reviewers independently screened and selected articles for extraction using Covidence and data were extracted from articles using study objectives. There were five studies that met the inclusion criteria. Four of the five studies reported on pain intensity and all studies reported on emotional functioning. Findings suggest art therapy interventions can be helpful for reducing pain, anxiety, stress, and fear associated with treatment. Further, there is emerging evidence that art therapy can support the management of acute and procedural pain in children. Future research should examine the impacts of integrating art therapy interventions into the multidisciplinary management of paediatric pain.